From Crisis to Recovery: Successful Experiences in the Eradication of Narcotics in Afghanistan Local Communities - YAR, Fayaz Gul Mazloum (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:Afghanistan, as one of the world’s largest producers of narcotics, faces significant social, economic, and health challenges. This research aims to identify and analyze the successful experiences in narcotics eradication in local Afghan communities and to evaluate the factors contributing to these successes.Methodology:A qualitative methodology was employed, utilizing semi-structured interviews with local community members, experts, and government officials. The data were analyzed using qualitative content analysis.Findings:The research findings indicate that educational programs, awareness-raising initiatives, the development of alternative economic opportunities, and active community participation have played crucial roles in reducing narcotics cultivation and consumption. Nevertheless, financial constraints, administrative corruption, and cultural resistance remain significant barriers to successfully implementing these programs.Implication:The study concludes that with increased international support, administrative transparency, and strengthened educational and economic programs, the dependency of local communities on narcotics cultivation can be significantly reduced. This research provides a foundation for the development of effective national policies in the fight against narcotics in Afghanistan.